2019
DOI: 10.1080/15592294.2019.1633867
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 upregulates the PI3K/AKT pathway through IGF1R and MYC in clinically aggressive chronic lymphocytic leukaemia

Abstract: EZH2 is overexpressed in poor-prognostic chronic lymphocytic leukaemia (CLL) cases, acting as an oncogene; however, thus far, the EZH2 target genes in CLL have not been disclosed. In this study, using ChIP-sequencing, we identified EZH2 and H3K27me3 target genes in two prognostic subgroups of CLL with distinct prognosis and outcome, i.e., cases with unmutated (U-CLL, n = 6) or mutated IGHV genes (M-CLL, n = 6). While the majority of oncogenic pathways were equally enriched for EZH2 target genes in both prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…Secondly, PTEN plays critical roles in regulating not only hematopoietic stem cell activity through a Niche-dependent mechanism, but also hematopoiesis and leukemogenesis [341][342][343]. Furthermore, TAL1, c-Jun, EZH2, TRIM22, ETV6/RUNX1, miR-7, -22, -26b, -103, -125b, -126, -139-5p, -181c, -193a, -628, and -3142, as well as LncRNA HULC, UCA1, linc00239 and LINC00265 control leukemogenesis, proliferation, apoptosis or chemoresistance via PI3K/AKT pathway [344][345][346][347][348][349][350][351][352][353][354][355][356][357][358][359][360][361][362][363]. Hereafter, PI3K/AKT pathway inhibition is regarded as a therapeutic approach [364,365] followed by the preclinical studies in leukemia cells [366,367] in spite of the upregulated expression of P2RY14 in acute leukemia cells resistant to PI3K/ mTOR inhibition [368].…”
Section: (Nct01002248; Nct01476137; Nct00881946) (Tables 2 and 3)mentioning
confidence: 99%
“…Secondly, PTEN plays critical roles in regulating not only hematopoietic stem cell activity through a Niche-dependent mechanism, but also hematopoiesis and leukemogenesis [341][342][343]. Furthermore, TAL1, c-Jun, EZH2, TRIM22, ETV6/RUNX1, miR-7, -22, -26b, -103, -125b, -126, -139-5p, -181c, -193a, -628, and -3142, as well as LncRNA HULC, UCA1, linc00239 and LINC00265 control leukemogenesis, proliferation, apoptosis or chemoresistance via PI3K/AKT pathway [344][345][346][347][348][349][350][351][352][353][354][355][356][357][358][359][360][361][362][363]. Hereafter, PI3K/AKT pathway inhibition is regarded as a therapeutic approach [364,365] followed by the preclinical studies in leukemia cells [366,367] in spite of the upregulated expression of P2RY14 in acute leukemia cells resistant to PI3K/ mTOR inhibition [368].…”
Section: (Nct01002248; Nct01476137; Nct00881946) (Tables 2 and 3)mentioning
confidence: 99%
“…Notably, EZH2 was recently shown to be capable to augment c-Myc transcriptional activity regardless of its methyl transferase activity. 22 In fact, analyzing public data (GSE115772 22 ) and datasets from the Open access and EZH2 that does not involve the methyltransferase activity of the latter one and which warrants further investigations.…”
Section: Notch-c-myc-facilitated Pd-l1 Induction Requires Ezh2mentioning
confidence: 99%
“…recruits MYC protein and binds to the IGF1R promoter to activate the transcription of IGF1R gene in a PRC2-independent manner, leading to the activation of its downstream PI3K/AKT signaling. 39 In adrenocortical carcinoma (ACC), EZH2 cooperates with transcription factor E2F1 to upregulate the expression of aggression-related genes, such as RRM2, PTTG1, and ASE1/PRC1, in a histone methyltransferaseindependent manner, thereby promoting the development of ACC. 40 Avni et al reported that polycomb proteins, such as YY1, Mel-18, Ring1A, EZH2, and EED, are recruited to the promoter of interleukin-4 (IL-4) and interferonγ (IFNγ), and induce the transcription of IL-4 and IFNγ cytokines in differentiated T helper cells.…”
Section: Ezh2 Act As Transcriptional Activator/ Coactivatormentioning
confidence: 99%